Reading, phonological memory and handwriting develop in parallel in the first years of school: evidence from a cross-sectional study - Pagliarini, Elena; Stucchi, Natale; Vernice, Mirta; Guasti, Maria Teresa (Graphos. Rivista internazionale di pedagogia e didattica della scrittura, 2022)
This study attempt to bring together the investigation of reading and writing, which have been traditionally considered separately. In particular, our cross-sectional study aimed at outlining the developmental trajectory of reading abilities and handwriting kinematic aspects of children in their first years of school. We collected reading, phonological memory and handwriting data from 102 Italian monolingual children ranging from Grade 1 to Grade 4 of primary school. Reading skills and phonological memory were assessed by means of standardized tests, whereas handwriting was assessed through the examination of a set of kinematic and dynamic descriptors collected by means of a digitizing tablet. The results of the present study provide evidence for a parallel developmental pathway of reading, phonological memory and handwriting (considering the motor features, not the spelling). The implications of these findings are discussed in the context of the understanding of developmental disorders and the influence of handwriting in learning to read.